Predicting Pandemic Curve Distribution Using Statistical Models - Eman Almuhur; Mona Khandaqji; Manal Al-labadi; Anwar Alboustanji (Institute of Medico-legal Publications Pvt Ltd, 2022)
This article discusses the distribution of pandemic in the world and pandemic curve in Jordan and how the science of probability and statistics predict when active cases tend to zero by determining the shape of epidemic curve and relating it to a special probability distribution that has specific measures and properties. At the beginning of the outbreak of any virus in a society, reliable data describing it and its spread will be rare, hence researchers set up statistical models that have the ability to predict the spreads’ shape, where the prospected people hosting such viruses will go to and the likelihood of transmitting it to places they travel. Those models use known statistical measures that estimate the probability of disease transmission from infected people to others. In addition, the factors related to roads and people’s movement, taking into consideration, public health interventions, such as wearing masks, closing places of people’s aggregations like schools, universities mosques and churches and quarantine make difference in numbers of infected people. The fundamental differences between the “Spanish flu” that attacked the world a hundred years ago and “Coronavirus” the world facing since the beginning of the current year 2020 is the amount of huge data concluded from scientific studies and reports related to virology and epidemiology.